Innovating Dance Learning through Interactive Video Media: The Case of Gandrung Seblang Lukinto Dance - Siti Wulandari; Sudarsri Lestari; Vina Rohmatul Ummah (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
This study was motivated by the limited availability of dance learning media in elementary schools that has not optimally integrated local culture into the learning process. The study aimed to develop a local wisdom-based interactive video media on the Gandrung Seblang Lukinto dance material, examine its feasibility, and analyze its effectiveness in dance learning at the elementary school level. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through expert validation questionnaires, student response questionnaires, and learning outcome tests. Data analysis was conducted using feasibility percentages, N-Gain, and paired sample t-tests. The findings revealed that the media achieved feasibility scores of 85% from material experts and 81.67% from media experts, categorized as feasible to highly feasible. Student responses reached 98.18%, indicating a very high level of practicality. The effectiveness analysis showed an N-Gain score of 0.78, while the paired sample t-test indicated a significant difference (p < 0.05). These findings demonstrate that the local wisdom-based interactive video media effectively helps students understand dance movements, increases learning engagement, and supports the preservation of local culture through dance learning in elementary schools.